Bridging the Gap: Using Consensus to Explore Entrustment Decisions and Feedback Receptivity in Competency-Based Emergency Medicine Residency Programs Through the Construction of a Q-Sample Incorporating a Delphi Technique - Chang, Yu-Che; Chuang, Renee S.; Hsiao, Cheng-Ting; Khwepeya, Madalitso; Nkambule, Nothando S. (Frontiers in Medicine, 2022)
Background: Recent changes in medical education calls for a shift towards student-centered learning. Therefore, it is imperative that clinical educators transparently assess the work-readiness of their residents through entrustment-based supervision decisions towards independent practice. Similarly, it is critical that residents are vocal about the quality of supervision and feedback they receive. This study aimed to explore the factors that influence entrustment-based supervision decisions and feedback receptivity by establishing a general consensus among clinical educators and medical residents, respectively. Methods: To explore these two paths, a four-step approach was taken: (1) literature search and interviews to generate opinion statements; (2) thematic analysis and grouping using three conceptual models; (3) translation; and (4) application of a Delphi technique to establish a consensus of the statements and validation for a subsequent Q-study. Results: A total of 585 and 1039 statements from the literature search and interviews were extracted to populate the concourse for clinical educators and emergency medicine residents, respectively. An expert panel of 11 clinical educators practicing in various specialties and another panel of 13 medical residents training in differing specialties were invited. After two-rounds of a Delphi technique, the clinical educator panel members agreed on 54 statements on factors that influence entrustment-based supervision decisions, while a total of 60 statements on the factors that influence feedback receptivity were retained by the medical resident panel. Conclusion: The implications of this study are two-fold. Firstly, establishing a general consensus on the factors that influence entrustment-based supervision decisions and residents’ feedback receptivity is necessary for cultivating transparency, which is essential in competency-based medical education. Secondly, this study contributes to the advancement of Q-methodology studies by extending literature on the rigorous approaches for constructing Q-samples. The implications of development of two Q-samples for exploring the diverse priorities of clinical educators when making entrustment-based supervision decisions and residents varied preferences for feedback receptivity are discussed.